Development of Comic Media on Changing form of Objects Material for Class IV SD Negeri 11 Betung Development of Comic Media on Changing form of Objects Material for Class IV SD Negeri 11 Betung - Dinanti, Tri; Sukardi, Sukardi; Putri, Mega Kusuma (Edumaspul: Jurnal Pendidikan, 2024)
Comics mean something interesting. One of the media developed by utilizing sophisticated technology is comic learning media. Developing comics in the right way and can produce comics according to the needs and characteristics of students. Comics are images that have an interesting storyline, which are easy to understand, and can make it easy for them to understand difficult material, The ADDIE development model (Analysis, Design, Development, Implementation, Evaluation) is a simple development model with a systematic research system that aims to formulate, improve, develop and produce a particular product. Data collection techniques have various ways of observation that have their own advantages depending on the purpose of the research, the source of the available data and the core context of the research being conducted. Interviews, Questionnaires Documentation Data analysis techniques Validity data analysis, practicality data. Potential effect analysis The results of the development of comic media on the material of changes in the form of objects for grade IV students in elementary schools are stated to be practical based on the results obtained through student response questionnaires with an average percentage value of 95% at the one-to-one stage, an average percentage value of 91% at the small group stage, and an average percentage value of 95.8% at the field test stage with very practical criteria. The results of the development of comic media on the material of changes in the form of objects for grade IV students in elementary schools are stated to be effective based on the results obtained through learning outcome tests that can be seen based on increasing student learning outcomes based on the average value of the pre-test is 32% and from the post-test is 86% with very effective criteria, this means that learning using this comic media has a potential effect so that it can be used in the learning process.